Star wars. The Clone wars, Captured - Valois, Rob (New York : Grosset & Dunlap, 2009)
Anakin Skywalker and Obi-Wan Kenobi have been captured by space pirates as well as Count Dooku, their archenemy, and now they must work together to escape
"Lucas Books."
"Based on the TV series Star Wars: The Clone Wars."
Keywords: Kenobi-Obi-Wan (Fictitious character) -- Juvenile fiction; Anakin, Skywalker (Fictitious character) -- Juvenile fiction; Prisoners -- Juvenile fiction; Science fiction